Employee creativity and innovation in higher education institutions: applying the dynamic componential model of creativity and innovation - Amoozegar, Azadeh; Esohwode, Oghenekevwe Erasmos; Yujiao, Wang; Pee, Wen Hui; Ismaeil, Ayman; Yadav, Mohit; Harun, Mohd Taib (Frontiers in Psychology, 2025)
IntroductionIn today's highly competitive landscape, higher education institutions must adopt innovative practices to thrive and maintain academic excellence. The engagement of academic staff is essential for driving such innovation. While previous studies have examined the influence of personal and workplace factors separately, this study investigates the roles of employee resilience, emotional intelligence, and job autonomy—alongside the mediating effect of employee creativity—on employee innovation in higher education, drawing on the Dynamic Componential Model of Creativity and Innovation.MethodsA quantitative research design was used, surveying 307 academic staff members from federal and state universities in South-Western Nigeria. The study employed a structural equation modeling approach via SmartPLS4 to test the hypothesized relationships among employee resilience, emotional intelligence, job autonomy, creativity, and innovation.ResultsThe findings confirm that employee resilience, emotional intelligence, and job autonomy significantly contribute to employee innovation. Additionally, mediation analysis reveals that both resilience and job autonomy foster innovation indirectly through employee creativity, whereas emotional intelligence does not exert a significant indirect effect.DiscussionThese results underscore the importance of cultivating resilience, autonomy, emotional intelligence, and creativity among academic staff as a strategic means to promote innovation within universities. They demonstrate that interventions emphasizing both personal growth and supportive work environments can meaningfully advance innovative practices and enhance academic excellence.